Study Of Physico-Chemical Characteristics of Patalganga River, Maharashtra, India - Ninad M. Marathe; Bhavita P. Chavan (Journal of Indian Fisheries Association, 2020)
Geographically, Maharashtra is divided into 5 basins Godavari, Tapi, Narmada, Krishna and the West flowing rivers of the Konkan region. Patalganga is one of the west flowing rivers which rises in the Matheran, branches near Khopoli and flows westward to join Dharamtar creek. Patalganga river is a significant source of water supply to Khopoli township, Khalapur area, Patalganga industrial area and nearly 40 villages in Raigad district. Patalganga is ecologically significant, harbours rich aquatic biodiversity. The Patalganga industrial Area is situated on the left bank of the river. Water from power projects, domestic sewage, industrial effluents- untreated or partially treated, often find their way into the river. Thus, The present study was undertaken to investigation the water quality parameters of the river. During the investigation, monthly water samples were collected from seven diﬀerent sites during January to June 2019, along the Patalganga river belt. The investigations on pH, temperature, dissolved oxygen, biological oxygen demand, chemical oxygen demand, NH3-N, nitrate, nitrite, phosphate and silica showed fluctuating levels of some parameters due to an increase in the pollutants in the water. Thus, in order to save the rich biodiversity, there is a need for necessary action to control the pollution in Patalganga river.